The influence of leadership, remuneration, competency on employee turnover intention with organizational culture as an intervening variable at Bank Ekonomi Rakyat Sejahtera Batam - Ngaliman, Ngaliman; Catrayasa, I Wayan; Lie, Lie (Goodwood Publishing, 2023)
Purpose: This study analyzes the influence of leadership, remuneration, and competence on employee turnover intention in BPR Sejahtera Batam, with organizational culture as an intervening variable. In the last five years, turnover intention in BPR Sejahtera Batam has increased significantly, reaching 21.05% in 2023. Research Methodology: This study employed a quantitative approach using census sampling of 111 employees. Primary data were collected through questionnaires with a Likert scale and analyzed using Partial Least Squares structural equation modeling (PLS-SEM) through SmartPLS 4. Results: Using primary data from 111 employees, this study found that leadership and competence did not significantly affect turnover intention, either directly or through organizational culture. In contrast, remuneration was shown to have a significant effect, highlighting the importance of compensation in employees' decisions to stay or leave the company. Organizational culture was not a significant mediator between remuneration and turnover intentions. Conclusions: Employees’ decisions to stay or leave are primarily determined by remuneration factors rather than leadership, competence, or organizational culture. Compensation aspects, such as salary, benefits, and bonuses, play a stronger role than other organizational factors in shaping turnover intentions. Limitations: This study focused on one organization with a relatively small sample size, which may limit the generalizability of the findings. Broader studies across multiple banks and regions are recommended. Contribution: This study provides practical insights for bank management to prioritize improvements in remuneration systems and employee welfare programs as effective strategies to reduce turnover intention.